Food Supply and Seawater pCO2 Impact Calcification and Internal Shell Dissolution in the Blue Mussel Mytilus edulis - Melzner, Frank; Stange, Paul; Trübenbach, Katja; Thomsen, Jörn; Casties, Isabel; Panknin, Ulrike; Gorb, Stanislav N.; Gutowska, Magdalena A. (PLoS ONE, 2011)
Progressive ocean acidification due to anthropogenic CO2 emissions will alter marine ecosytem processes. Calcifying organisms might be particularly vulnerable to these alterations in the speciation of the marine carbonate system. While previous research efforts have mainly focused on external dissolution of shells in seawater under saturated with respect to calcium carbonate, the internal shell interface might be more vulnerable to acidification. In the case of the blue mussel Mytilus edulis, high body fluid pCO2 causes low pH and low carbonate concentrations in the extrapallial fluid, which is in direct contact with the inner shell surface. In order to test whether elevated seawater pCO2 impacts calcification and inner shell surface integrity we exposed Baltic M. edulis to four different seawater pCO2 (39, 142, 240, 405 Pa) and two food algae (310–350 cells mL−1 vs. 1600–2000 cells mL−1) concentrations for a period of seven weeks during winter (5°C). We found that low food algae concentrations and high pCO2 values each significantly decreased shell length growth. Internal shell surface corrosion of nacreous ( = aragonite) layers was documented via stereomicroscopy and SEM at the two highest pCO2 treatments in the high food group, while it was found in all treatments in the low food group. Both factors, food and pCO2, significantly influenced the magnitude of inner shell surface dissolution. Our findings illustrate for the first time that integrity of inner shell surfaces is tightly coupled to the animals' energy budget under conditions of CO2 stress. It is likely that under food limited conditions, energy is allocated to more vital processes (e.g. somatic mass maintenance) instead of shell conservation. It is evident from our results that mussels exert significant biological control over the structural integrity of their inner shell surfaces.